1992
DOI: 10.3109/07853899209166998
|View full text |Cite
|
Sign up to set email alerts
|

Familial Dyslipidaemic Hypertension and Other Multiple Metabolic Syndromes

Abstract: Data from several different studies are reviewed suggesting that a subset of hypertension is associated with metabolic abnormalities involving lipids, insulin, and often obesity, all aggregating strongly in families. Persons with 'familial dyslipidaemic hypertension (FDH)' have an especially high risk of early coronary disease. The clinical and biochemical features of FDH are compared with Reaven's Syndrome X, familial combined hyperlipidaemia, dense LDL subfractions, diabetes, impaired glucose tolerance, cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

1995
1995
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 14 publications
1
12
0
1
Order By: Relevance
“…The coronary mortality rate was approximately four-fold higher in the hypertensive patients with dyslipidaemia than in those without it. 22 A better understanding of the specific atherogenic determinants in these patients will provide targeted strategies for the detection, prevention and intervention of CVD. The purpose of the study is to examine the differences in insulin resistance and postprandial TG response, both associated with CVD, between hypertensive patients with or without hypertriglyceridaemia.…”
Section: Figure 1 Results Of the 75-g Oral Glucose Tolerance Tests (Omentioning
confidence: 99%
“…The coronary mortality rate was approximately four-fold higher in the hypertensive patients with dyslipidaemia than in those without it. 22 A better understanding of the specific atherogenic determinants in these patients will provide targeted strategies for the detection, prevention and intervention of CVD. The purpose of the study is to examine the differences in insulin resistance and postprandial TG response, both associated with CVD, between hypertensive patients with or without hypertriglyceridaemia.…”
Section: Figure 1 Results Of the 75-g Oral Glucose Tolerance Tests (Omentioning
confidence: 99%
“…In this study, children with three or more variables at the bottom quartiles dis- played a significantly lower prevalence of metabolic syndrome later in adulthood, reflecting a phenomenon of "tracking at low levels." An individual's genetic diathesis may play an important role in maintaining the clustering at low levels from childhood to adulthood (25)(26)(27). On the other hand, the association between childhood clustering of risk variables at low levels and adulthood metabolic syndrome, independent of family history of CV diseases (surrogate markers of genetic susceptibility), also underscores the importance of lifestyles in early life for CV risk in adulthood.…”
Section: Results -mentioning
confidence: 99%
“…In another example, heterozygote relatives of in view of the features of type I hyperlipoproteinemic humans, type I hyperlipoproteinemic probands tend to be hypertriglyceri-and careful evaluation of the differences between these two demic, but this is associated with confounding variables such phenotypes should provide novel insights into fat transport and as advancing age and other risk factors for hypertriglyceridemia, energy metabolism. We have also shown that the offspring of including adiposity and glucose intolerance (14). The observa-LPL-deficient mice crossed with tissue-specific LPL transgenic tions reported here in the heterozygous LPL-deficient mouse mice are viable, such mice provide an opportunity to study indicate that a primary deficiency in the LPL gene causing the effects of expression of LPL in various tissues on plasma half-normal total body LPL is sufficient to cause a significant lipoproteins as well as energy metabolism.…”
Section: Methodsmentioning
confidence: 99%
“…A similar lipoprotein profile has been described in the cld mouse (8), which is both LPL and hepatic lipase deficient due to a mutation affecting lipase processing and secretion (9). Humans with heterozygous LPL deficiency have a tendency to hypertriglyceridemia with advancing age, obesity, and diabetes, as well as during metabolic stress (10)(11)(12)(13)(14). LPL deficiency has been suggested as a cause of familial combined hyperlipoproteinemia (FCHL) a condition characterized by increased VLDL and LDL levels due at least in part to increased hepatic secretion of apo B-containing lipoproteins (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%